We the people a concise introduction to American politics - Patterson, Thomas E. (McGraw-Hill Higher Education, 2008)
American political culture: seeking a more perfect union; Constitutional democracy: promoting liberty and self-government; Federalism: forging a nation; Civil liberties: protecting individual rights; Equal rights: struggling toward fairness...